Establishing the best combination of the kappa free light chain index and oligoclonal bands for an accurate diagnosis of multiple sclerosis - Monreal, Enric; Fernández-Velasco, José Ignacio; García-Soidán, Ana; Sainz de la Maza, Susana; Espiño, Mercedes; Villarrubia, Noelia; Rodríguez-Jorge, Fernando; Chico-García, Juan Luís; Sainz-Amo, Raquel; Masjuan, Jaime; Costa-Frossard, Lucienne; Villar, Luisa María (Frontiers in Immunology, 2023)
The immunoglobulin kappa free light chain (KFLC) index has been proposed as a potentially suitable alternative to oligoclonal IgG bands (OCGB) for diagnosing multiple sclerosis (MS), offering automation and reduced processing time. However, there is no consensus on the preferred approach or how to combine both techniques. This prospective cohort study aimed to determine the best utilization of OCGB and KFLC index in patients with a clinically isolated syndrome (CIS) followed for at least two years. OCGB and KFLC were assessed using isoelectric focusing and immunoblotting and turbidimetry, respectively. Sensitivity, specificity, and accuracy for diagnosing MS were calculated for each method. The study included 371 patients, with 260 (70.1%) being women, and a median age of 34.9 (27.8–43.9) years. Using a cut-off value of 6.1, the KFLC index demonstrated a sensitivity and specificity of 86.3% and 93.9%, respectively. The sensitivity of OCGB (95.3%) was higher (p < 0.001 vs. KFLC index) and the specificity (100%) was comparable to that of the KFLC index (p = 0.5). The concordance between the methods was not uniform across all patients, with 97.8% agreement in patients with KFLC index ≥6.1 and 56.0% in patients with KFLC index <6.1. In patients with a KFLC index <6.1, OCGB still identified 75.0% of MS patients due to its higher sensitivity. An algorithm using the KFLC index as a screening tool and OCGB as an alternative for patients with a negative KFLC index result achieved an accuracy of 96.3%. Thus, combining the KFLC index and OCGB can provide an easily reproducible and accurate method for diagnosing MS, with OCGB primarily reserved for patients with a KFLC index <6.1.